Tеrminology of information culture in the context of modern library practices - Lomachinskiy Bohdan (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2023)

(untitled)
The purpose of the article is to determine the specifics of the terminology of information culture in the context of modern library practices in the conditions of globalization challenges of digitization. The research methodology is based on acombination of system analysis, which made it possible to consider various manifestations of information culture in the library as a complex information and communication system, a dialectical method of cognition, which involves acomprehensive analysis of the conceptual apparatus of information culture due to the contradictory relationships of its various aspects, the comparative method allowed to single out specific features of individual research concepts. The scientific novelty consists in expanding ideas about the main scientific approaches to the specifics of using the terminology of information culture in the context of library activities. Conclusions. Information culture is represented by the integrity of spiritual and practical development of the world, which combines methods, technologies of creation and use of intellectual innovations in the field of science, culture, education and material production. The transformation of modern libraries from repositories of humanity's intellectual resources to centers of active information and communication flows necessitates the expansion of the essence of information culture as a means of forming not only cultural but also intellectual capital (creative abilities, creative way of thinking, moral values, etc.). Information culture should ensure a person not only his information freedom, but also form responsibility for ensuring the principles of information security of other members of society. At all historical stages, the activities of libraries were interconnected with information and communication processes in society, acting ast heir driving force and logical result. Based on the analysis of Ukrainian legislation, the content essence of the main concepts that reveal the specificity of the phenomenon of information culture is determined. The conclusions emphasize that the complication of the phenomenon of information culture in the library space is caused by the formationof a new library user - a digital person. A digital person is a carrier and interpreter of ahuge amount of information, but has a low level of critical thinking and a lack of interest in fundamental knowledge. The model of information culture of a modern library can beunderstood at three levels - personal, group and public, which are aimed at expanding the possibilities of knowledge service and facilitating the process of knowledge management.